Assessing PFAS exposure in Rocky Mountain elk (Cervus canadensis nelsoni) populations adjacent to the former Rocky Flats nuclear site: A preliminary analysis - David Lucas; Kelsey E. Schreiber; Joseph M. Halseth; Meghan C. W. Williams; Philip Sorensen; Benjamin R. Kraft; Megan E. Klosterman; Thomas J. Ronning; Wayne Soong; Monique A. Rivera (PLoS ONE, 2025)
The Rocky Flats National Wildlife Refuge is located west of Denver, Colorado, USA along the central Front Range of the Rocky Mountains. The wildlife refuge property includes a former U.S. Department of Energy nuclear weapons facility, hereafter “the former Rocky Flats site.” Owing to the storage and use of aqueous film forming foam (AFFF) at the on-site fire department, industrial areas of the former Rocky Flats site has detectable concentrations of per- and polyfluoroalkyl substances (PFAS) in groundwater (range perfluorooctanesulfonic acid [PFOS]: not detected [ND] [<0.75]–350 ng/L, perfluorooctanoic acid [PFOA]: ND [<0.55]–160 ng/L) and surface water (range PFOS: 1.9–18 ng/L, PFOA: ND [<0.55]–13 ng/L). AFFF is a known source of PFOA and PFOS contamination in the environment. PFAS are a class of thousands of human-made chemicals considered ubiquitous in the environment globally. Exposure to these chemicals can negatively impact the health of both humans and wildlife. In March 2023, we used a draft version of the U.S. Environmental Protection Agency Method 1633 to analyze liver and muscle tissues from 17 Rocky Mountain elk ( Cervus canadensis nelsoni ) to detect the presence of PFAS. We collected samples from 15 elk residing at the former Rocky Flats site and 2 elk at locations with no known PFAS contamination (i.e., control locations). Neither PFOA nor PFOS was detected in elk muscle tissues collected at the former Rocky Flats site or the control locations. The average method detection limits for PFOA and PFOS in muscle tissues were 0.166 ng/g and 0.154 ng/g respectively. PFOS was detected within 100% of the liver tissues harvested from elk at the former Rocky Flats site and both control locations. The average PFOS concentrations in liver tissues collected at the former Rocky Flats site and control locations were 16.23 ± 4.40 ng/g (maximum concentration 34.20 ng/g) and 8.75 ± 3.02 ng/g (maximum concentration 9.40 ng/g), respectively. To the best of our knowledge, this is the first study examining PFAS concentrations in elk. Although we were unable to draw conclusions owing to the relatively small sample size, PFOS concentrations in liver tissues collected at the former Rocky Flats site were low, consistent with those detected in other species of wildlife studied in the United States with known PFAS contamination.